Managing Change in Organizations / Third Edition - Carnall Colin A (Prentice Hall, 1999)
This book offers a through and practical overview of how to achieve effective organizations. Business Transformation, Management Structures and Management in Action, Organizations in the Twenty-First Century: The Value-Added Organization, The Learning Organization, Sustaining Organizational Effectiveness, Managing Complexity, Leadership in Practice, Managing Organizational Change, Diagnosing Change, Managing Major Changes, Programs of Change, Learning from Change, A Strategy for Effectiveness, Strategies for Corporate Transformation.